Self-medication practices in a rural population in Tamil Nadu - Mariappan, Veerakumar Arumugam; Ananthan, Velmurugan Anbu (International Journal Of Community Medicine And Public Health, 2020)
Background: Self-medication is one of the harmful practices of growing concern where health care facilities are out of reach in the rural population. So, this study was carried out to know about the prevalence of self-medication and the type of drugs commonly used and the reason for self-medication. Methods: A cross-sectional study was conducted among 150 subjects in Out-patient department of a rural primary health centre, Sirugambur during April and May 2016. A pretested semi-structured questionnaire was used after obtaining informed consent. It was analysed using SPSS trial version 20. Univariate analysis was done. P value <0.05 was considered statistically significant. Results: Majority of the study population were in the age group of 18-30 years (38.6%), followed by 31-45 years (36.7%). The prevalence of self-medication use was 78.7% (n=118). Among those, 111 (74%) were getting medicines from medical shop directly. The common reasons for going to medical shop was easy accessibility (52.3%), immediate response (22.5%), and familiarity (18%). The most common source of drug information reported was pharmacist and friends (76.6%), followed by media (21%). The drugs commonly used were paracetamol (42%), antibiotics (32.1%) and antihistamines (16%). Conclusions: The prevalence of self-medication use was high in the study population. Self-medication is one of the components of self-care adopted by the WHO. The drug regulatory and health authorities have to increase awareness among the general public especially in rural areas on the pros and cons of responsible self-medications to eventually improve their attitudes towards the practices of self-medication.